Slowing of World Economy Growth: Analysis of Key Reasons - Taranov, Petr V.; Basenko, Alexander M.; Roshchina, Lydia N.; Kulikova, Irina V.; Ukraintseva, Inna V.; Samygin, Sergei I. (International Journal of Criminology and Sociology, 2022)
The article is devoted to the analysis of the key reasons for the slowdown in the global economy. According to the analysis, the slowdown in the global economy is caused by the following seven key reasons: trade wars and the aggravation of trade relations in the international economic market; global instability and technological uncertainty; risks of increased financial uncertainty; the impossibility on the part of some countries to overcome the consequences of the global crisis and the sanctions policy of the West; reformatting of economic activity in a political manner; wave of debt accumulation in developing countries; slowdown in labor productivity growth. The authors conclude that the global economic slowdown trend has a long-term perspective.